Inkubasi Bisnis Lokabadra sebagai Embrio Ketahanan Ekonomi Rumah Tangga Desa Mlese, Kecamatan Gantiwarno, Kabupaten Klaten, Provinsi Jawa Tengah - Putri, Wika Harisa; Kresnanto, Nindyo Cahyo; Raharti, Rini; Andari, Eni (Penerbit Goodwood, 2024)
Purpose: Mlese Village is one of the villages in the Klaten Regency with a relatively strong local cultural base. Although most of the population works as farmers, local cultural preservation activities are maintained in community life. Mlese Village has a Lokabadra cultural art park built as a center for creative industry development to facilitate community interests. This art and culture park was made to be an activity center, creative industry development center, and business incubator for the village. However, because the growth rate of the business incubator is yet to be optimal, community groups who support business units need to receive assistance and increase their personal capacity to optimize the use of the Lokabadra Cultural Arts Park area. Methodology: This community service activity was carried out at the Mlese Village Cultural Park and aimed at the Lokabadra youth group. This workshop and mentoring was attended by 21 people and held for a full day. To maximize the benefits of this activity, the supporting community is also involved, so that all parties have a harmonious vision in developing Lokabadra business activities. Results: Three materials were prepared to conduct workshop activities: marketing strategy, business-space arrangement, product quality, and product presentation enhancement. The culinary development sector, one of Lokabadra's commercial sectors, was the focus of this workshop. During the workshop, attendees engaged in active consultation with resource individuals to deliberate on matters such as business space layout design, product display plans, and marketing media. The results of this activity were immediately implemented by rearranging business locations and product packaging. Limitations: Limited time, funds, synchronization, and harmonization of agendas between the parties to support the optimization of the Mlese village business incubator center are the main limitations of this program. Contribution: This mentoring activity contributes to increasing the skills and insight of the supporting community in optimizing Lokabadra's role as the business incubation center of Mlese Village.